Analisis Implementasi Program Kampus Mengajar Angkatan Tiga dalam Meningkatkan Kemampuan Literasi di SD Negeri 3 Ngabeyan Sukoharjo 2023 - Purwaningsih, Yesti; Khasanah, Latifah Nur; Yunus, Muhammad (Jurnal Abdimas Multidisiplin, 2024)
Purpose: The aim of this research was to analyze the implementation of a third-generation teaching program to improve students' literacy skills at SD Negeri 3 Ngabeyan Sukoharjo. Methodology/approach: This study used qualitative field research methods with descriptive-analytic data analysis. Results: The results of this research state that the optimization of libraries in these schools is still weak, as evidenced by the lack of a workforce, absence of e-literacy, and minimal book collections. The implementation of learning on campus is carried out in three stages: planning, implementation, and evaluation. At the planning stage, students make learning plans but do not create a learning syllabus. The learning methods used in implementing learning are the Reading Aloud method, tutorial guidance, lectures, card sorting, problem-solving, reward and punishment, and project-based learning market days. We then evaluated learning using formative and summative assessments. Limitations: To focus on one goal to produce maximum results, this research is limited to developing the literacy skills of students at SD N 3 Ngabeyan. Literacy includes the ability to read, write and count Contribution: This research has theoretical and practical contributions. Theoretically, this research can be one of the developments in literacy science and can be a reference source for further research. Practically, this research can contribute to elementary school educational institutions in general in developing students' literacy skills and become a guide for students in subsequent campus teaching programs. Novelty: This research found that the campus program teaching the third generation at SD N 3 Ngabeyan was very significant in improving students' literacy skills. This is proven by changes in students' abilities before and after the program.